Seismic hazard analysis of tailings ponds in Honghe Prefecture based on information quantity model and analytic hierarchy process - Li, Siyang; Cao, Yanbo; Huang, Xin; Xu, Yufan; Luo, Manhao; Li, Sheng (Frontiers in Earth Science, 2025)
Honghe Prefecture in Yunnan Province is rich in mineral resources, with a large number of tailings ponds distributed extensively. Located in the southern segment of the Xiaojiang fault zone, it has complex geological structures and frequent seismic activities, making it one of the high seismic risk areas in China. Under seismic action, tailings ponds may trigger secondary disasters such as dam failure and tailings leakage, posing severe threats to the environment and socio-economy. This study identifies the spatial distribution characteristics and disaster-causing mechanisms of tailings ponds by analyzing seismic hazard factors, and constructs a hazard assessment model using GIS spatial analysis, information quantity model, and analytic hierarchy process (AHP) to generate a seismic hazard zoning map of tailings ponds. Twelve evaluation indicators for seismic geological hazards and eight factors for tailings pond seismic hazards are selected. By integrating multi-source data, quantifying the correlation between each indicator and disasters, and determining factor weights, a comprehensive evaluation model is formed. Based on the results, prevention and control strategies such as dam reinforcement and monitoring early warning are proposed. The results show that tailings ponds with low hazard are mostly distributed in geologically stable areas, while those with medium to high hazard are concentrated in eastern Gejiu City, southern Jianshui County, and southern Mile City, significantly affected by factors such as fault zone activities. The research results not only provide a scientific basis for the safety management of tailings ponds but also offer technical support for seismic resistance management and disaster prevention in other earthquake-prone areas.